Toward Reducing the Operation Temperature of Solid Oxide Fuel Cells: Our Past 15 Years of Efforts in Cathode Development - Yang, Guangming; Su, Chao; Shi, Huangang; Zhu, Yinlong; Song, Yufei; Zhou, Wei; Shao, Zongping (Energy & fuels, 2020)
The development of clean and efficient energy conversion and storage systems is becoming increasingly vital as a result of accelerated global energy consumption. Solid oxide fuel cells (SOFCs) as one key class of fuel cells have attracted much attention, owing to their high energy conversion efficiency and low emissions. However, some serious problems appeared because of the scorching operating temperatures of SOFCs (800–1000 °C), such as poor thermomechanical stability and difficult sealing, resulting in a short lifespan and high cost of SOFCs. Therefore, lowering the operating temperature of SOFCs to mid-range and even low range has become one of the main goals for SOFC development in the recent years. Looking for new cathode materials with high electrocatalytic activity and robust stability at relatively low temperatures is one of the essential requirements for intermediate-to-low-temperature SOFCs (ILT-SOFCs). During the past 15 years, we put considerable efforts into the development of alternative cathode materials for ILT-SOFCs. In this review, we give a summary of our progress from such efforts. We first summarize several strategies that have been adopted for developing cathode materials with high activity and durability toward reducing operating temperatures of SOFCs. Then, our new ideas and progress on cathode development with respect to activity and stability are provided. Both the cathodes of oxygen-ion-conducting SOFCs and protonic-conducting SOFCs are discussed. In the end, we outline the opportunities, challenges, and future approaches for the development of cathodes for ILT-SOFCs.